Evidence for Vertical Transmission of Novel Duck‐Origin Goose Parvovirus‐Related Parvovirus. Issue 3 (18th February 2016) - Chen, H.; Tang, Y.; Dou, Y.; Zheng, X.; Diao, Y.
Summary: In 2015, novel duck‐origin goose parvovirus‐related parvovirus (N‐GPV) infection progressively appeared in commercial Cherry Valley duck flocks in North China. Diseased ducks were observed to have beak atrophy and dwarfism syndrome (BADS). A previous study showed that a high seropositive rate for N‐GPV indicated a latent infection in most breeder duck flocks. To investigate this possibility in hatching eggs collected from N‐GPV‐infected breeder ducks, 120 eggs were collected at various stages of embryonic development for viral DNA detection and an N‐GPV‐specific antibody test. N‐GPV DNA was present in nine hatching eggs, eleven duck embryo and eight newly hatched ducklings. Of the newly hatched ducklings, 58.33% (21/36) were seropositive. Further, two isolates were obtained from a 12‐day‐old duck embryo and a newly hatched duckling. N‐GPV infection did not reduce the fertilization rate and hatchability. These results indicate possible vertical transmission of N‐GPV and suggest that it may be transmitted from breeder ducks to ducklings in ovo .